Estudo comparativo do alinhamento rotacional do componente tibial na artroplastia total do joelho com manutenção ou ressecção da gordura retropatelar - Rodrigo Barreiros Vieira (2019)
INTRODUCTION: The removal of retropatellar fat pad during total knee arthroplasty is a procedure performed by most of the surgeons in order to facilitate joint exposure, leading to greater precision in the positioning of the tibial component. However, in recent decades, authors have concluded that maintenance of retropatellar fat pad leads to better clinical and functional outcomes and fewer surgical wound complications. OBJECTIVES: This study aims to evaluate whether the maintenance of retropatellar fat pad influences the rotational alignment of the tibial component, the surgical time and to verify the state of insertion of retropatellar fat pad in the tibia after the procedure. METHODS: This is a cross-sectional, randomized, double-blind intervention study involving 50 patients divided into two equivalent groups, one with the maintenance of retropatellar fat pad and the other with its complete removal. Rotational alignment according to the Berger method, surgical time and degree of involvement of the retropatellar fat pad insertion in the tibia were evaluated. RESULTS: Retropatellar fat pad had been partially injured in 84% and completely in 16% of the knees, and the greatest internal rotation positioning of the tibial component occurred in patients with partial injury of the fat pad compared to its complete disinsertion (p 0.02). In knees with more advanced arthrosis, surgical time was longer in patients in whom the retropatellar fat pad was preserved compared to its complete removal (p 0.002). Longer surgical time was also identified in knees with more advanced arthrosis compared with milder arthrosis among patients with maintenance of retropatellar fat pad (p 0.013). CONCLUSION: It was concluded that the maintenance of retropatellar fat pad did not interfere with the rotational alignment of the tibial component, there was a longer surgical time in patients with maintenance of retropatellar fat pad associated with advanced arthrosis and retropatellar fat pad was disinserted, at least partially in all cases.